Discrimination and Identity. An approach from the false recognition of Charles Taylor - Barquet Muñoz, José (2021)
This paper seeks to approach the impact of discrimination on the development of identity. The reflection is carried out from the theoretical perspective of Charles Taylor, considering his concepts of recognition and false recognition, as well as Judith Butler's contributions related to gender identity. As an example, discrimination towards sexual and gender diversity groups is considered, seeking to improve the level of explanation. In conclusion, it is highlighted the importance of analyzing discrimination not only because of the short-term impact it has on people, but also because of the way in which this social unrest affects the full development of individuals in the future.